Bilateral muscle oxygenation kinetics in response to repeat sprint cycling in strong and weak individuals - Abbott, J. C. (Electronic Theses and Dissertations. Paper 3696, 2021)
Repeat sprint ability has been investigated thoroughly, however optimal training methodology to improve RSA remains elusive. Both kinetic and physiological viewpoints have been used to scrutinize aspects of RSA including, initial sprint performance (anaerobic power), maximal cardiorespiratory fitness (VO2max), lactate threshold, anaerobic capacity (mean power), muscle activation (EMG), and local muscle oxygenation kinetics. To our knowledge no study has utilized maximal strength levels as a separate factor among a homogenous group of cardiorespiratory fitness individuals (as determined by peak VO2 during RSA). The purpose of this study was to better understand the relationship between maximal strength, muscular characteristics, and cycling RSA- respective to muscle oxygenation responses. Fifteen participants completed fifteen 10-second maximal effort sprints on a cycle ergometer interspersed with 30-seconds passive recovery. Respiratory, muscle oxygenation, and kinetic responses were monitored continuously and evaluated relationships with maximal strength and muscular architecture as determined by isometric mid-thigh pull and ultrasonography respectively. A series of 2 x 15 mixed design, group x time, ANOVA`s were used to evaluate the effects of group and or sprint on muscle oxygenation kinetics. Strong individuals were found to have significantly greater levels of muscle oxygenation usage, recovery and the respective rates; p = 0.01, p = 0.02, p <0.01, p = 003. In conjunction, stronger individuals displayed 3 significantly greater anaerobic power and capacity throughout fifteen consecutive sprints. Lastly, linear regression with stepwise selection, found muscular strength and size to account for 73% of the variance of RSA, removing muscular pennation angle and VO2max . The results suggest that maximal strength is influential to RSA and should be an area of focus for repeat sprint ability training.